AI Perspectives - Kirchner, Frank; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer.)
AI Perspectives covers the application of AI in industry, healthcare, transport, education, social sciences and humanities, and business and economics. We use a strict high-level selection process to ensure an excellent publication quality. AI Perspectives publishes innovative applications of artificial intelligence with a focus on an in-depth description how basic research enabled the application, how applied research triggers new questions for basic research, and how integration of various AI methods in application can be achieved. This includes articles discussing the interaction of data driven vs. model driven AI, system oriented and integrated research, and the responsibility, ethics, explainability, and transparency of AI. Topics of interest include, but are not limited to: Machine perception and multi-media sensing Autonomous vehicles Intelligent and cooperative interacting robots Speech recognition and language use Cyber-physical systems, hybrid teams and Industry 4.0 Knowledge representation Medical diagnosis and rehabilitation robots Process improvement and AI strategies for digital businesses AI in legal and Fintech industries Internet of Things Regulation and ethics.
Keywords: Engineering; Technology and Engineering